2021
DOI: 10.1002/cam4.4191
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal PD‐1/PD‐L1 inhibitors for the first‐line treatment of non‐small‐cell lung cancer with high‐level PD‐L1 expression in China

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The standard distribution models simulating the long-term survival of patients diagnosed with cancer have been widely applied in economic evaluations on immuno-oncology therapies. A majority of previous studies ( Liu et al, 2021 ; Teng et al, 2021 ; Kang et al, 2022 ) which undertook indirect comparison overlooked the issue of PH and performed NMA by assuming the HRs remain constant as time went by, calculating survival data in treatment groups depending on the constant HR. However, with breakthroughs in immunotherapy, the survival of cancer patients probably have changed and the hazard function is foreseenably becoming more complex.…”
Section: Discussionmentioning
confidence: 99%
“…The standard distribution models simulating the long-term survival of patients diagnosed with cancer have been widely applied in economic evaluations on immuno-oncology therapies. A majority of previous studies ( Liu et al, 2021 ; Teng et al, 2021 ; Kang et al, 2022 ) which undertook indirect comparison overlooked the issue of PH and performed NMA by assuming the HRs remain constant as time went by, calculating survival data in treatment groups depending on the constant HR. However, with breakthroughs in immunotherapy, the survival of cancer patients probably have changed and the hazard function is foreseenably becoming more complex.…”
Section: Discussionmentioning
confidence: 99%
“…First, negotiate a lower price for the drug and put it on the Medicare list. One study showed that atezolizumab, when reduced in price by 80%, may have a cost-effective advantage at a WTP threshold of US$32 517/QALY 31. Same as serplulimab, sintilimab, a domestic PD-1, was launched in China at the end of 2019 with a price as high as US$1132.74.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that atezolizumab, when reduced in price by 80%, may have a cost-effective advantage at a WTP threshold of US$32 517/QALY. 31 Same as serplulimab, sintilimab, a domestic PD-1, was launched in China at the end of 2019 with a price as high as US$1132.74. In just 2 years, the price dropped to US$156.08, a whopping 86% drop.…”
Section: Discussionmentioning
confidence: 99%
“…Drug price information was acquired from the local bid-winning price (Drugdataexpy) ( 20 ), which is equal to the drug prices for most Chinese hospitals. Other information was sourced from the existing literature ( 14 , 15 , 27 - 33 ). Based on an assumption of a mean area of 1.72 m 2 of the patient’s body surface, we calculated the drug dosage for chemotherapy in each cycle ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Drug price information was acquired from the local bid-winning price (Drugdataexpy) (20), which is equal to the drug prices for most Chinese hospitals. Other information was sourced from the existing literature (14,15,(27)(28)(29)(30)(31)(32)(33).…”
Section: Costmentioning
confidence: 99%